2017
DOI: 10.1016/j.neuroscience.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

CART peptide in the nucleus accumbens regulates psychostimulants: Correlations between psychostimulant and CART peptide effects

Abstract: In this study, we reexamined the effect of CART peptide on psychostimulant (PS)-induced locomotor activity (LMA) in individual rats. The Methods utilized were as previously published. The PS-induced LMA was defined as the distance traveled after PS administration (intraperitoneal), and the CART peptide effect was defined as the change in the PS-induced activity after bilateral intra-NAc administration of CART peptide. The experiments included both male and female Sprague-Dawley rats, and varying the CART pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…But, it was also found that injection of CART peptide tended to stimulate or increase the activity of animals who did not respond to PSs (Figure 1). This finding reinforced our earlier hypothesis that CART peptides in the NAc regulate the action of PSs and dopamine [2,10]; when the PS effect on LMA was a significant increase, CART peptide inhibited the LMA, and conversely, when PS had little or no effect on LMA, CART peptide stimulated LMA. Thus, CART peptide seems to act to maintain PS-induced LMA within a certain window of activity.…”
supporting
confidence: 89%
See 4 more Smart Citations
“…But, it was also found that injection of CART peptide tended to stimulate or increase the activity of animals who did not respond to PSs (Figure 1). This finding reinforced our earlier hypothesis that CART peptides in the NAc regulate the action of PSs and dopamine [2,10]; when the PS effect on LMA was a significant increase, CART peptide inhibited the LMA, and conversely, when PS had little or no effect on LMA, CART peptide stimulated LMA. Thus, CART peptide seems to act to maintain PS-induced LMA within a certain window of activity.…”
supporting
confidence: 89%
“…In summary, a new analysis of data on the effects of CART peptide on cocaine-induced LMA [10] supports the previous hypothesis that CART regulates the effects of PSs, and also shows that CART peptide exhibits a rate dependency.…”
supporting
confidence: 68%
See 3 more Smart Citations